Nilai-Nilai Sufistik dalam Proses Terapi Pikiran Mind Healing Technique - Rizki Fadilah (Jurnal Riset Agama, 2021)
Recently, there has been an interesting phenomenon regarding mind therapy, the Mind Healing Technique, which is an alternative therapy for healing various types of physical and psychological ailments. The purpose of this study is to analyze Sufism values in the Mind Healing Technique process of mind therapy, a case study on student anxiety in facing school exams at SMPN 1 Simpang Teritip Bangka Belitung. This research method uses a qualitative research type, where the data sources come from the results of observations, interviews and other literature related to the research theme. Based on the results of the research that MHT (Mind Healing Technique) mind therapy is not only effective in healing students' anxiety in facing school exams, MHT (Mind Healing Technique) mind therapy also has significant sufistic values. Therefore, researchers highly recommend MHT (Mind Healing Technique) mind therapy as an alternative to physical and psychological healing.